Clinical use of platelet-rich fibrin in the repair of non-healing incision wounds after fibular fracture surgery: A case report. Issue 50 (17th December 2021) - Lin, Xingzhen; Zhu, Manhua; Yuan, Juan; Zhi, Fang; Hou, XinJu
Abstract: Rationale: This report describes rehabilitation for a 53-year-old female recovering from non-healing skin and soft tissue defect after distal tibial open fracture by using platelet-rich fibrin topical repair following an automobile accident. Patient concerns: The patient was admitted to a rehabilitation specialty hospital approximately 1 year post a fracture of the distal left tibiofibula and separate surgical tibiofibular fracture incision and internal fixation + bone grafting. Diagnoses: Clinical presentation included the left ankle incision was interrupted for about 3 cm with poor healing, a small amount of muscle necrosis, fat liquefaction, a large amount of yellow purulent secretion overflow and necrotic material was seen in the local wound. Interventions: Platelet rich fibrin (PRF) gel was injected into the wounds and submerged sites to make full contact with the wounds and close the wounds with the autologous platelet-rich fibrin prepared by mixing, and then covered with oil gauze to keep the wounds moist and promote granulation growth. The outermost layer was covered with cotton pads. Outcomes: After 30 days of 2 PRF treatments, the skin defect was healed and no significant abnormality was observed at 6 months follow-up. Lessons: Treatment with topical autologous platelet-rich plasma gel Significantly accelerates the healing of wounds, shortens healing time, improves healing quality and reduces scar formation without significant adverse effects.